Contrasting characteristics of psychosis in outpatients with borderline personality disorder or schizophrenia at a tertiary care institution - Hernández-Velázquez, Mario; Díaz-Anzaldúa, Adriana; Arango, Iván; Rosel-Vales, Mauricio; Celada-Borja, César (Frontiers in Psychiatry, 2024)
Summary and objectivesBorderline personality disorder (BPD) and schizophrenia can present with psychotic symptoms, such as delusions and hallucinations. This study, conducted at a tertiary care center, compared the characteristics of psychotic symptoms in patients diagnosed with BPD and patients diagnosed with schizophrenia, as well as the prevalence of self-harm, suicide attempts, and hospitalizations within these groups.MethodIn this comparative study, 50 individuals diagnosed with BPD and 50 with Schizophrenia, aged between 18 and 45 years, were assessed for intensity of psychotic symptoms with the Psychotic Symptom Assessment Scale (PSYRATS) and the Cardiff Abnormal Perceptions Scale (CAPS). Data were analyzed with IBM SPSS v25.0.ResultsOn the PSYRATS, the schizophrenia group scored higher in auditory hallucinations and in the number of voices, while in the BPD group the auditory hallucinations score was correlated with the number of suicide attempts (P=0.025). On the CAPS, the BPD group showed higher scores on positive abnormal perceptions in all dimensions compared to the schizophrenia group (P=0.002).ConclusionsOur study suggests that patients with BPD experienced a more intense burden of psychotic-like experiences compared to those with Schizophrenia, with a greater frequency, interference, and distress reported. Although patients with Schizophrenia had higher scores on the PSYRATS, the BPD group’s scores were also notable, and a correlation was identified between auditory hallucinations and suicide attempts in the BPD group.